Penerapan Good Corporate Governance (GCG) Pada Bank Pembiayaan Rakyat Syariah (BPRS) - Shakinah, Putri; Satria, Danu; Gunawan, Dandi; Nasution, Juliana (Universitas Labuhanbatu, 2022)
The purpose of this study is to examine and analyze how the implementation of Good Corporate Governance (GCG) in Islamic People's Financing Banks (BPRS) and formulate new legal arguments relating to the regulation of Good Corporate Governance (GCG) in BPRS. The method used in this research is normative juridical law and the legal material analysis technique used consists of descriptive analysis and content analysis. The results of the study explain that the implementation of Good Corporate Governance is very much needed by Islamic People's Financing Banks (BPRS) to build public trust as an absolute requirement for the banking world to develop properly and healthily. Improving the quality of the implementation of Good Corporate Governance needs to be implemented because the risks and challenges faced by banks both internally and externally are increasingly complex.